Molecular crosstalk in perivascular adipose tissue: mechanisms of inflammation, metabolic dysregulation, and therapeutic opportunities in cardiovascular disease - Zhang, Shunhong; Jiang, Jun; Luo, Yi; Liu, Guangyue; Hu, Saidi; Wan, Siran; Luo, Chenchen; Li, Hong; Li, Nian; da Graça Espírito Santo Vasconcelos, Jailson; Lavres Ceita de Carvalho, Leonilde; Lima Bragança da Costa, Monazeri; et al. (Frontiers in Cardiovascular Medicine, 2025)
The escalating recognition of perivascular adipose tissue (PVAT) as a molecular nexus in cardiovascular disease (CVD) pathogenesis necessitates a comprehensive synthesis of its spatiotemporal dynamics and therapeutic potential. This review synthesizes PVAT's roles in vascular inflammation, metabolic dysregulation, and emerging diagnostic strategies, emphasizing molecular cross-talk and spatial heterogeneity. We explore PVAT's molecular interactions in obesity, diabetes, and hypertension, elucidating its contribution to inflammation, oxidative stress, and endothelial dysfunction. Advanced imaging techniques, notably the perivascular fat attenuation index (FAI) and circulating biomarkers, are highlighted for early CVD detection. Novel therapeutic strategies, including lifestyle modifications, pharmacological interventions, and gut microbiota modulation, are discussed. Finally, we emphasize multi-omics approaches and propose a roadmap bridging basic and clinical research to advance PVAT-based CVD management.